¿Cómo aprendemos desde la neurociencia? : la neuropedagogía y el impacto en el aula de clase - Mendoza Carrasco, Mariella Victoria (2015)
The neuropedagogy is a science, whose object of study iseducation and the human brain, understood as a socialbody, which can be modified by the pedagogical practice.In this sense, it’s essential that educators understand thenew approaches of the theories of the brain. This articlediscusses the need to generate a complex change in theway they teach these days; the mission is to discoverthe enormous power of neurotransmitters to stimulatestudents in the classroom.